Health care seeking behaviuor among the elderly in Hue City - Nguyen Hoang, Lan; Tran Thi Thanh, Nga; Le Thi Bich, Thuy (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objectives: the study is to investigate health care seeking behaviour and to identify factors associated those behaviour among elderly living in Hue city, Vietnam. Methods: 400 old persons who suffered from health problem in the past one month were interviewed directly at their house by a structured questionnaire to survey health care seeking behaviour. Multivariate logistic regression models were applied to identify factors affecting health care seeking behaviour among participants. Results: 72.5% of respondents sought treatment services for their acute illness in the past one month and 68% of them used prevention services in the past one year before the interview. In general, source of income, educational level and severe level of disease influenced health care seeking behaviour among participants. Conclusions: The findings revealed limitation of the elderly to access health care services, especially health preventive services in Hue city. The identified associated factors can help formulate effective public health programs to improve health status among the elderly in Hue city as well as in the country in general.